Reduksi Semen Dengan Campuran Fly Ash Dan Kapur Terhadap Kuat Tekan Dan Kuat Tarik Belah Beton - Nur, Muhammad Alfian; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
The use of concrete in construction continues to increase each year, leading to a rise in cement prices as the primary component of concrete. Given this situation, this study aims to reduce cement demand while utilizing waste materials, such as Fly Ash and lime, to partially replace cement. This research examines the effect of partially replacing cement with reduction levels of 5%, 10%, and 15%, substituted with a mixture of Fly Ash and lime in proportions of 75%:25%, 50%:50%, and 25%:75% for each reduction level. The target compressive strength of the normal concrete is 25 MPa. The results indicate that using Fly Ash and lime impacts the compressive and split tensile strength of concrete. At a 5% cement reduction with 75% Fly Ash and 25% lime, the compressive strength increased by 0.74% compared to normal concrete. In split tensile testing, optimal improvement was achieved at a 5% cement reduction with 25% Fly Ash and 75% lime, showing a 1.85% increase compared to normal concrete. This study demonstrates that partially replacing cement with Fly Ash and lime not only reduces cement usage but also enhances concrete performance, making it a promising alternative for sustainable construction.